NON-POINT SOURCES (NPS) POLLUTION MODELLING AND WATER QUALITY IMPROVEMENT USING WETLAND - Sapari, Nasiman; Adlan, M.N. (2009)
River water quality in urban environment is under serious threat of pollution from many sources including residential, commercial, industrial, and recreational areas. Significant amount of pollution load is contributed by the non-point sources. A river in an urban area of Kuala Lumpur namely the Damansara River was modelled using a computer simulation(MUSIC software) to predict the quality of the water during wet and dry seasons. The scope of the simulation is to predict the concentration levels of Total Suspended Solid (TSS), Total Nitrogen (TN) and Total Phosphorus (TP). Prediction on pollutants reduction by wetlands as a pollution control for the river catchments was also made using the model. The model is based on the information from hydrological conditions and land use data. The predicted results from this simulation were compared against results from a physical laboratory-scale wetland. The predicted water quality indicates that the downstream part of the catchments can be classified as Class IV. These results are in agreement with the Department of Environment (DOE) and The Department of Irrigation and Drainage (DID) classification for the stretch of the river which is Class IV. In order to improve the quality of the river to the level of Class II, intervention by using wetlands was chosen and the percentage of pollution reduction was predicted. As a comparison, a laboratory-scale wetland was constructed and operated. The results of pollutants reduction by the laboratory-scale wetland were found comparable to the results obtained from the computer model. The predicted reduction for TSS, TP and TN were 51.7%, 51.4% and 51.4% while the reduction in the laboratory-scale wetland were 56.9%, 43.6% and 44.3% respectively. The difference between the two systems is less than 10%. Water quality improvement of the Damansara River from Class IV to Class II is likely to be feasible as shown by the results from both computer modelling and laboratory model of wetlands